Analysis of the Needs for the Development of Indonesian Culture and Storytelling Based on BIPA Animation Video Teaching Materials - Diana, Laksmi; Arum, Dewi Puspa; Susanto, Gatut; Angoluan, Krisha Camille (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2025)
The growing global interest in learning Indonesian necessitates effective and engaging teaching materials for foreign speakers (BIPA/Bahasa Indonesia bagi Penutur Asing). However, traditional BIPA instruction faces challenges, including low student motivation, limited speaking skills, and insufficient integration of Indonesian cultural elements, leading to suboptimal learning outcomes. To address the gaps, this qualitative needs analysis investigates the specific requirements of international students and instructors for storytelling-based animated video teaching materials that incorporate Indonesian culture. Data were collected through purposive sampling, interviews, questionnaires, and observations across six research stages. The study aimed to identify key elements for BIPA materials that enhance speaking skills and motivation while fostering a deeper cultural understanding. Findings reveal that language needs, cultural background, learning styles, storytelling elements, and Indonesian cultural integration influence international students' preferences for BIPA teaching materials. Incorporating these elements into material design will boost effectiveness and appeal. This study concludes that storytelling-based animated videos effectively bridge linguistic competence and cultural comprehension in BIPA learning, contributing to innovative, student-centric materials.